2011
DOI: 10.1002/pmic.201100171
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary pressure reduction attenuates expression of proteins identified by lung proteomic profiling in pulmonary hypertensive rats

Abstract: The present study was designed to analyze protein expression in lungs from pulmonary hypertensive rats in order to identify novel signaling pathways. This was achieved by proteomic studies in which proteins from lung homogenates from hypoxic were compared to normoxic rats. The expression of these proteins was then investigated in lungs from hypoxic rats treated with either an activator of soluble guanylyl cyclase, BAY 412272, or an inhibitor of phosphodiesterase type 5, sildenafil. The proteomic study revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Kwapiszewska and co-workers used a shotgun proteomic approach to identify chloride intracellular channel 4, as a novel multifunctional protein involved in angiogenesis and several signalling pathways implicated in pulmonary arterial hypertension 17 . Recently, lung proteome profiles of chronic hypoxic rats with pulmonary hypertension were compared with normoxic rats using 2D-based proteomics approach to identify the novel signalling pathways involved in the pathophysiology of pulmonary hypertension 18 . Most recently, Olmeda et al reported a proteomic approach to describe the changes in protein complement induced by moderate long-term hypoxia (rats exposed to 10% O 2 for 72 h) in BAL and lung tissue, with a special focus on the protein associated with pulmonary surfactant 19 .…”
mentioning
confidence: 99%
“…Kwapiszewska and co-workers used a shotgun proteomic approach to identify chloride intracellular channel 4, as a novel multifunctional protein involved in angiogenesis and several signalling pathways implicated in pulmonary arterial hypertension 17 . Recently, lung proteome profiles of chronic hypoxic rats with pulmonary hypertension were compared with normoxic rats using 2D-based proteomics approach to identify the novel signalling pathways involved in the pathophysiology of pulmonary hypertension 18 . Most recently, Olmeda et al reported a proteomic approach to describe the changes in protein complement induced by moderate long-term hypoxia (rats exposed to 10% O 2 for 72 h) in BAL and lung tissue, with a special focus on the protein associated with pulmonary surfactant 19 .…”
mentioning
confidence: 99%
“…In addition, CLIC5 is up-regulated in lungs from pulmonary hypertensive rats by proteomic studies 22 . In patients with nonischaemic dilated cardiomyopathy, reduced expression of CLIC3 is founded through microarray mRNA analysis 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Østergaard et al [42] created proteomic profiles of lung homogenate from hypoxic versus normoxic rats, followed by proteomic profiling of hypoxic rats treated with either an activator of soluble guanylyl cylase BAY 412272 or a PDE5 inhibitor (sildenafil), with the goal of hypothesis generation regarding signaling pathways of PH. Several proteins were found to be upregulated in the hypoxic rat lung, including guanine nucleotide binding protein B, GSTw1, cathepsin D, chloride intracellular channel subunit 5, annexin A4, F actin capping protein capZ, and the translation factor elongation factor 1 delta.…”
Section: Proteomic Analysis Of Ph Using Animal Modelsmentioning
confidence: 99%
“…Animal studies have provided a foundation for analysis of the PH lung proteome in a variety of contexts for PH, including acute onset of PH [39], chronic exposure in a hypobaric hypoxic environment [40,41], monocrotaline lung injury (in which administration of a toxic plant alkaloid induces delayed and progressive lung injury with resultant PH), hemodynamic alterations, and various treatments affecting phosphodiesterase 5 or guanalyl cyclase [42]. Adult studies of IPAH and familial pulmonary arterial hypertension (FPAH) have built on these animal studies, substantiating several previously identified proteins in human lung, as well as identifying new proteins of interest.…”
Section: Review Of the Ph Proteome: What Is Known From Animal Adultmentioning
confidence: 99%